Spectral, electrochemical and calculated properties of quadrupolar chromophores based on tetrafluorobenzene - Pippig, Falko; Mikysek, Tomáš; Ramaiyan, Manikannan; Pytela, Oldřich; Kulhánek, Jiří; Vytřas, Karel; Almonasy, Numan; Bureš, Filip (University of Pardubice, 2014)
Absorption/emission and electrochemical properties of four new quadrupolar push-pull-push molecules with central tetrafluorobenzene acceptor and two peripheral N,N-dihexylamino and O-hexyloxy donor groups were investigated. Experimental data were completed with quantum-chemical calculations. The extent of the intramolecular charge-transfer and nonlinear optical properties were elucidated in terms of structure-property relationships. The electronic nature of the appended donor group, length, planarity and composition of the B-linker (combination of 1,4-phenylene, 2,5-thienylene and acetylenic subunits) are the most important factors affecting the linear as well as nonlinear optical properties.